How the Graduate LIS Professionals Cope with Constant Need for Updating Their Knowledge and Skills: A Croatian Case - Aparac, Tatjana; Vrana, Radovan; Dragija, Martina Badurina, Boris (2001)
The objective of the paper is to give an overview of the existing CPE programs for the Croatian LIS professionals and to research how the LIS graduates cope with the constant need to update their professional knowledge and skills. The focus of the paper is on challenges that the Croatian LIS graduates face at their work places. The paper also reports results of a survey carried out among the LIS professionals who graduated at the Department of Information Sciences at the University of Zagreb, Croatia, in the period 1995-2000. During that period a number of changes occurred in the LIS field as well as in the Croatian society. In order to highlight main problems in CPE for LIS graduates and to establish a starting point for a further discussion on the issue, the authors conducted a survey among all reachable LIS graduates working in libraries and different information agencies (82 questionnaires were sent out and some interviews were conducted). Special attention was paid to needs of the LIS graduates related to CPE, their opinion of courses currently offered, and their suggestions for the improvement of existing CPE programs.
Projekt MZOS
ENG